COHORT EFFECTS IN MULTIMORBIDITY AMONG OLDER US ADULTS: DIFFERENCES BY RACE/ETHNICITY AND NATIVITY. (20th December 2022) - Bishop, Nicholas; Haas, Steven; Quiñones, Ana
Abstract: Multimorbidity (≥ 2 co-occurring chronic health conditions) affects > 50% of US adults aged 65 and older. Building on emerging work suggesting greater risk of multimorbidity in more recent cohorts of aging Americans, we examine heterogeneity in cohort-patterns of multimorbidity by race/ethnicity and nativity. Observations were drawn from the Health and Retirement Study (1998–2018) including adults aged 51 and older across 7 birth cohorts (born < 1924, 1924–1930, 1931–1941, 1942–1947, 1948–1953, 1954–1959, and 1960–1965). Multimorbidity was measured using a sum of 9 possible chronic conditions (heart disease, hypertension, stroke, diabetes, arthritis, lung disease, cancer, high depressive symptomatology, and cognitive impairment). Linear mixed models adjusting for age, period, and cohort effects tested whether cohort-specific multimorbidity risk varied for US-born White, US-born Black/African American, US-born Hispanic/Latino, and foreign-born Hispanic/Latino older adults. 30, 607 adults contributed 158, 727 total observations, grand mean age was 65.40 (SD=10.07), and mean multimorbidity was 2.18 (SD=1.60). US-born Black/African Americans had the greatest multimorbidity burden regardless of cohort. US-born Hispanic/Latinos experienced the highest cohort-related increases in multimorbidity, followed by US-born Black/African Americans. For example, compared to US-born Hispanic/Latinos born 1931–1941, US-born Hispanic/Latinos born 1954–1959 had 1.03 (CI: 0.78;1.28) more expected chronic conditions. Foreign-born Hispanic/Latinos had the smallest cohort-related increases in multimorbidity. Our results document heterogeneity in rising rates of multimorbidity across cohorts, suggest that US-born minority adults in Baby Boom cohorts may be at especially high risk of multimorbidity, and confirm protective effects of immigrant status among Hispanic/Latino older adults.